Diamond wire cutting: A methodology to evaluate stone workability. Issue 9 (4th July 2017) - Zichella, Lorena; Bellopede, Rossana; Marini, Paola; Tori, Alice; Stocco, Alessandro
ABSTRACT: The economic relationship between the companies that produce multi-wire cutting machines and the stone slab producers is based on the classification of the rocks, mainly determined by the users themselves, that take into account the relative ease of cutting. This classification is principally based on the cutting speeds (feed and peripheral), which are obviously correlated with stone properties and cannot be evaluated before the working phase. The aim of this study is to use inexpensive and simple tests to make, before cutting, a cuttability prediction of the new stone in order to avoid dangerous and expensive cutting endeavors when an unknown stone is being worked upon. In order to predict stone workability, the results of ultrasonic pulse velocity and Knoop micro-hardness on 18 different types of stone was correlated. Seven classes were drawn as follows : from 1 (easier to cut rocks) to 7 (harder to cut rocks). The results of this rock cuttability scientific classification provide a good correlation with the industrial classification.